2019
DOI: 10.1097/pec.0000000000001740
|View full text |Cite
|
Sign up to set email alerts
|

Bone Fractures in Children With Cholestatic Liver Disease May Mimic Those Seen in Child Abuse

Abstract: Certain fractures in children are highly specific for child abuse.Metabolic bone disease frequently develops in patients with cholestatic liver disease (CLD); this can result in weakened bones and a predisposition to pathologic fractures. Fractures that occur in patients with rickets and osteopenia may mimic a bone response to inflicted injury, which in children raise the concern of child abuse. Here we report a series of 15 patients with CLD who developed pathologic fractures in the setting of metabolic bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In contrast, a recent study of 238 patients with PSC found no correlation between osteoporosis and age, disease duration, or severity of disease but rather a correlation between bone mineral density and bone reabsorption and T helper 17–cell frequency 358. Bone disease is associated with nontraumatic fractures representing a significant source of morbidity before and after LT as well as reduced quality of life 359–361. Therefore, all patients with PSC should be screened for metabolic bone disease by bone density measurement at diagnosis and then every 2–3 years in those with normal bone mineral density (Figure 7).…”
Section: Management Of Pscmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a recent study of 238 patients with PSC found no correlation between osteoporosis and age, disease duration, or severity of disease but rather a correlation between bone mineral density and bone reabsorption and T helper 17–cell frequency 358. Bone disease is associated with nontraumatic fractures representing a significant source of morbidity before and after LT as well as reduced quality of life 359–361. Therefore, all patients with PSC should be screened for metabolic bone disease by bone density measurement at diagnosis and then every 2–3 years in those with normal bone mineral density (Figure 7).…”
Section: Management Of Pscmentioning
confidence: 99%
“…[358] Bone disease is associated with nontraumatic fractures representing a significant source of morbidity before and after LT as well as reduced quality of life. [359][360][361] Therefore, all patients with PSC should be screened for metabolic bone disease by bone density measurement at diagnosis and then every 2-3 years in those with normal bone mineral density (Figure 7). [362][363][364] Guidance statements 26.…”
Section: Ibd Managementmentioning
confidence: 99%
“…In addition, metabolic bone diseases such as rickets and osteopenia can predispose children to fractures mimicking abuse [ 31 ]. Children with cholestatic liver disease (CLD) have malabsorption of fat soluble vitamins and increased bone fragility due to poor bone mineralization that can lead to mimics of abuse [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Birth trauma such as subdural hemorrhage from vacuum-assisted and cesarean section delivery can also be mistaken for abuse [ 32 ]. Furthermore, abusive head trauma (AHT) from “shaken baby syndrome” is another common finding in child abuse [ 31 ]. Metabolic disorders such as glutaric aciduria (GA1) or Menkes disease and bleeding disorders such as Factor XIII or vitamin K deficiency can mimic “shaken baby syndrome [ 33 , 34 ]”.…”
Section: Discussionmentioning
confidence: 99%